DO FAIR VALUE DECISIONS INCREASE IDIOSYNCRATIC RISK? - Firmansyah, Amrie; Pamungkas, Pria Aji; Prakosa, Dani Kharismawan; Purwaka, Adhitya Jati; Bachtiar, Muchamad Izaaz Hannun (Kesatuan Press, 2023)
Systematic and non-systematic risk can both cause investment risk. Internal company conditions typically cause non-systematic risk. Diversification can help to mitigate this risk. This research aims to look into applying fair value to idiosyncratic risk. This quantitative study employs secondary data from manufacturing financial statements and stock data from the IDX. In addition, this study uses monthly data on 10-year government bond yields. Information on financial statements was obtained from www.idnfinancials.com, stock prices from www.finance.yahoo.com, and monthly 10-year government bond yields from www.bloomberg.com. In total, 575 observations were used in this study (firm-year). We used multiple linear regression analysis on panel data to test the research hypothesis. The study finds that managers' fair value accounting relates to idiosyncratic risk. The results of this test apply to both the market and the Fama-French models. This study contributes to knowledge development concerning fair value testing, which still needs to be improved in developing countries.